2017
DOI: 10.1016/j.fsigss.2017.09.191
|View full text |Cite
|
Sign up to set email alerts
|

Ancestry characterization of Ecuador’s Highland mestizo population using autosomal AIM-INDELs

Abstract: Ancestry Informative Insertion-Deletion markers have been used as a tool to infer the origin of population. In the present study, we report the results obtained for 46 AIM-INDELS in the Ecuadoŕs highland population by analyzing 171 unrelated individuals. Native American was the most prevalent ancestry in the studied population (63.1%), followed by European (30.3%) and lastly African (6.6%). The admixture found is in agreement with the historical background of Ecuador.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 6 publications
2
10
1
2
Order By: Relevance
“…Our patient came from Coca city in the Amazon region of Ecuador; according to the ancestry profile of the Ecuadorian population [ 12 ] she is a Mestizo: 63.1% Native American, 30.3% European, and 6.6% African ancestry. The first contact with our patient was in April 2016 at 11-months old, she was the second child of non-consanguineous healthy parents.…”
Section: Case Presentationmentioning
confidence: 99%
“…Our patient came from Coca city in the Amazon region of Ecuador; according to the ancestry profile of the Ecuadorian population [ 12 ] she is a Mestizo: 63.1% Native American, 30.3% European, and 6.6% African ancestry. The first contact with our patient was in April 2016 at 11-months old, she was the second child of non-consanguineous healthy parents.…”
Section: Case Presentationmentioning
confidence: 99%
“…In Ecuador, there are studies about the ancestral origin, for instance, the Ecuadorian was reported to be composed of 59.6% of Native American, 28.8% of European and lastly 11.6% of African origin (14) (15).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ecuadorian self-identified as: "mestizos" 71.9%, "montubios" 7.4%, Afro-Ecuadorian 7.2%, "indígenas" 7%, "blancos" 6.1% and others (0.4%) (13). There are also reports of the Ecuadorian ancestry using AIMs in mestizo population where Native American was the most prevalent ancestry (59.6%), followed by European (28.8%) and lastly African (11.6%) (14) (15).…”
Section: Introductionmentioning
confidence: 99%
“…La encuesta evidenció el resultado de la "colonización" europea: el mestizaje (INEC 2010). Los ecuatorianos somos mestizos y la genética lo confirma (Zambrano et al 2017).…”
Section: Los Genes Ecuatorianosunclassified
“…Al analizar la ancestría en más de dos mil individuos mestizos, indígenas y afros, los resultados demostraron que en promedio, los mestizos están compuestos por 61% (+23) de genes indígenas, 32% caucásicos (+13), y 7% (+3) afroecuatorianos. Analizando la ancestría, específicamente, de la sierra del Ecuador mostró datos de 63,1% de nativos americanos, 30,3% de europeos y 6,6% de africanos (Paz-Y-Miño 2014; Zambrano et al 2017). Para el ADN mitocondrial se determinó que pertenecemos a la variante ancestral amerindia A y B (Paz-Y-Miño 2014; Baeta et al 2012;Paz-Y-Miño et al 2016).…”
Section: Los Genes Ecuatorianosunclassified